Sistem Pendukung Keputusan Evaluasi Kinerja Pegawai pada Dinas Pekerjaan Umum Bengkulu Selatan Menggunakan Simple Additive Weighting Method - Reswan, Yuza; Prabowo, Dedy Agung (Jurnal Media Infotama, 2018)
The decision support system for employee performance evaluation at the South Bengkulu public works department is very useful because it can provide another alternative for decision makers to select suitable employees to fill vacant positions. The use of a decision support system for employee performance evaluation using the simple additive weighting method is expected to reduce subjectivity in decision making. Instead, a calculation will be carried out on all employee assessments, so that it is hoped that employees with the best abilities will be selected. The research aims to create a decision support system for evaluating public service performance of employees at the South Bengkulu public works department. The benefits of this research can provide another alternative for decision makers to select suitable employees to fill vacant positions.